Systematic Literature Review: Family Economics Education as an Effort to Enhance Family Economic Resilience Based on Local Culture - Hutamy, Ericha Tiara; Safutri, Rezi; Putri, Salsabila; Afryan, Muhammad Aqiel Rifky; Hasan, Muhammad (Universitas Muhammadiyah Mataram, 2023)
This research aims to examine the importance of economic education in a family environment based on local culture in an effort to increase family economic resilience. In the context of globalization and social change, families need to understand and adapt to economic principles that are relevant to everyday life. Local culture provides a strong foundation for shaping family economic thinking and behavior. One of the key aspects of family economic education is the development of economic literacy and good economic behavior. This research uses the PRISMA 2020 systematic literature review method, utilizing Scopus and Google Scholar as research databases, with search results obtaining 239 articles (Scopus = 39 articles with a time period of 2018–2022, and Google Scholar = 200 articles with a time period of 2018–2022). Then, selection and evaluation are carried out to obtain relevant articles. Meanwhile, data collection uses a systematic review by analyzing research manuscripts obtained from Google Scholar that have been indexed nationally and internationally in the last five years, which aims to answer research questions by summarizing various research results. In facing modern challenges, the existence of the traditions of the Kajang Tribe applies the principles of Tallasa Kamase-masea and Pasang as a strong foundation in all aspects of human life. Apart from that, these traditions also become the pride and identity of the Kajang Ammatoa indigenous people, strengthening the continuity of their culture in an environment that continues to develop. Based on the research results, it was found that economic education in the family acts as a catalyst to increase the family's economic resilience.